POST MORTEM FORAMINIFERA DISTRIBUTION IN ACEH WATER POST-TSUNAMI - Ricky Rositasari; Bambang S. Soedibjo (JOURNAL OF COASTAL DEVELOPMENT, 2008)
The oceanographic research in Nangroe Aceh Darussalam waters post-tsunami was conducted on September 2006. Foraminifera which easily found as element of marine sediment was used as a tool to understand the trace effect of tsunami to marine sediment on the research area. Foraminifera is a single cell organism which has hard cover (test) as a primitive skeleton, that would remain in sediment for a long periods. Samples were carried out from west, north and east part of Nangroe Aceh Darussalam (NAD) Province waters using box-corer. The result showed there have been a mass of energy that force the sediment sliding and triggered the mixture of shallow and deep species of foraminifera in research area, particularly in western part of the waters.